Visual Evaluation of Soil Structure (VESS) Method to Assess Soil Properties of Agroforestry System in Pangalengan, West Java - Bima Dwi Siswanto Aji; Nurheni Wijayanto; Basuki Wasis (Jurnal Manajemen Hutan Tropika, 2021)
Agroforestry is an alternative land use that not only provides benefits in economic aspects, but also in ecological aspects including improving soil quality. This research aims to evaluate the physical quality of soil in various types of land use, including agroforestry systems and evaluate the efficiency of the VESS method in determining soil physical quality. This study uses the VESS method to analyze soil quality in six land uses in Pangalengan, West Java (i.e. agroforestry, forest, tea plantations, coffee plantations, agriculture cultivation, and abandoned land). It used The VESS method because it has been widely applied in many countries, but has never been applied in Indonesia. Soil property parameters (BD, soil porosity, soil permeability, and SOC) were measured to correlate with the VESS score. VESS score ranged from 1 (good soil quality) to 5 (poor soil quality). The VESS score for each land type ranged from Sq 1.3–4.33. The soil quality in agroforestry (Sq 1.89–2.04) is not much different from natural forest (Sq 1.3). The VESS score has strong correlation (r) with soil property parameters (BD = 0.97, soil porosity = -0.97, soil permeability = -0.83, SOC = -0.94). A Strong correlation value indicates that the VESS method can be used to analyze soil quality.